Islamic economic principles and the adoption of accounting information systems: perceptions of ease of use and usefulness in Indonesian MSMEs - Solikhatin, Firda Aprilia; Saadah, Naili; Agriyanto, Ratno (Journal of Islamic Economics Management and Business (JIEMB), 2024)
The Accounting Information System (SIA) is an important component in supporting the running of a business, especially in simplifying the financial recording process. The use of SIA can provide various benefits and convenience for its users. However, among Micro, Small, and Medium Enterprises (MSMEs), the use of SIA is still relatively low, due to various factors. This study aims to test and analyze the influence of perceived ease of use and perceived usefulness on the use of SIA in MSMEs, by integrating Islamic economic values such as fairness, efficiency, and transparency in financial management. These values play an important role in encouraging users to choose a system that not only facilitates the work process, but is also in line with sharia principles. This study uses primary data obtained through surveys, as well as secondary data from the Tegal Regency Cooperatives, SMEs, and Trade Office. The research sample consisted of 100 respondents who were MSME actors in Tegal Regency, with a sampling technique using the purposive sampling method. The independent variables in this study were perceived ease of use and perceived usefulness, and data analysis was carried out using multiple linear regression tests. The results showed that perceived ease of use and perceived usefulness partially had a positive and significant effect on the use of SIA. Simultaneously, these two variables also affect the use of SIA. The integration of Islamic economic values in the use of SIA has the potential to increase the awareness and commitment of MSME actors to a more efficient and transparent system, in accordance with Islamic principles